Computational study of clot formation in aneurysms treated with shape memory polymer foam. (January 2020) - Horn, John D.; Maitland, Duncan J.; Hartman, Jonathan; Ortega, Jason M.
Highlights: Computational modeling was used to predict short-term aneurysm treatment outcomes. Open-celled embolic foam stimulates complete thrombus occlusion within 5–10 min. Clotting response is independent of foam pore size or orientation. Foams appear to elicit a more favorable and predictable response than current treatments. Abstract: To prevent aneurysmal rupture, intracranial aneurysms are often treated with endovascular metal coils that fill the aneurysm sac and stimulate thrombus formation, thereby isolating the aneurysm from the arterial flow. Despite its widespread use, this method can result in suboptimal outcomes leading to aneurysm recurrence. Recently, shape memory polymer foam has been proposed as an alternative aneurysm filler. In this work, a computational thrombus model is used to predict the clotting response within idealized 2D aneurysms virtually treated with foam. The results are compared to previously reported clot formation predictions in identical 2D aneurysm geometries filled with simplified endovascular metal coil shapes. Each of the foam-filled aneurysms reached at least 94% thrombus occlusion regardless of foam pore size or orientation, whereas the final thrombus occlusion within the coil-filled aneurysms varied from 80.8 to 92.2% with many of the cases leaving large areas in the aneurysm neck unfilled. Based on the simulations presented here, shape memory polymer foams may be able to produce more predictable, uniform, and complete clotting results than bare metal coils, independent of foam geometry or orientation.